2004
DOI: 10.1007/s00120-004-0592-8
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Akupunktur als Third-line-Therapie bei prim�rer Enuresis nocturna

Abstract: Laser acupuncture is a painless, non-invasive, and cost effective treatment for children with therapy resistant monosymptomatic nocturnal enuresis. This kind of acupuncture is an alternative treatment with positive results. Currently, we are treating 24 children (22 males, 2 females) out of a planned 200 children aged between 5 and 12 years. These patients have had a classic monosymptomatic nocturnal enuresis. Up to now, school medicine therapy has been unsuccessful. Over 3 months, we treated the children once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Heller et al. (2004) reported that 21 out of 24 kids (87.5%) experienced less frequent enuresis after being treated with LA. Six of the 24 children (25%) were dry before the completion of the 12th treatment, and 16 (66.6%) had an enuresis frequency that had decreased by more than half by the end of the 12th treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heller et al. (2004) reported that 21 out of 24 kids (87.5%) experienced less frequent enuresis after being treated with LA. Six of the 24 children (25%) were dry before the completion of the 12th treatment, and 16 (66.6%) had an enuresis frequency that had decreased by more than half by the end of the 12th treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Most children were dry, indicating increased vasopressin production at night after laser acupuncture and consequently, a decrease in urine production. Heller et al (2004) reported that 21 out of 24 kids (87.5%) experienced less frequent enuresis after being treated with LA. Six of the 24 children (25%)…”
Section: Subjects Characteristicsmentioning
confidence: 99%